18. IMPACTS OF ARTIFICIAL VENTILATION ON SOME PULMONARY MECHANICAL INDICES AND BLOOD OXYGEN IN EXTRACORPOREAL CIRCULATION IN CORONARY SURGERY PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the impact of artificial ventilation on some pulmonary mechanical indices and blood oxygen in extracorporeal circulation in coronary surgery patients.Subjects and methods: A clinical, prospective, controlled study on coronary artery patients with indications for coronary artery bypass graft surgery at 175 Military Hospital from January 2022 to May 2023.Results: Pulmonary protective artificial ventilation while running on an external circulatory system improves the blood oxygenation index of coronary surgery patients. The group of patients receiving cardiopulmonary bypass while running the extracorporeal circulation had the PaO2/FiO2 index at the time of extracorporeal circulation and after resuscitation (356.3 ± 29.9 and 344.9 ± 38.56, respectively) was higher than the group without non-artificial ventilation (the PaO2/FiO2 index was 342.9 ± 28.44 and 326.9 ± 35.34, respectively) (p < 0.05).Conclusion: Protective artificial ventilation of the lungs while running the extracorporeal circulation improved blood oxygenation index for coronary surgery patients with extracorporeal circulation.
Keywords: Artificial ventilation; pulmonary mechanical index; blood oxygen; extracorporeal circulation; coronary surgery